Early hemodynamic impact of SGLT2 inhibitors in overweight cardiometabolic heart failure: beyond fluid offloading to vascular adaptation– a preliminary report - Nadia Salerno; Jessica Ielapi; Angelica Cersosimo; Isabella Leo; Assunta Di Costanzo; Giuseppe Armentaro; Salvatore De Rosa; Angela Sciacqua; Sabato Sorrentino; Daniele Torella (Cardiovascular Diabetology)
Abstract Background Heart failure (HF) is increasingly recognized as a heterogeneous cardiometabolic disorder, often in the context of overweight/obesity independently from diabetes. Sodium-glucose cotransporter-2 inhibitors (SGLT2i) reduce HF hospitalizations and cardiovascular mortality across ejection fraction (EF) categories, yet their early hemodynamic effects in cardiometabolic HF, and with preserved ejection fraction (HFpEF) in particular, remain underexplored. Methods A prospective, single-center study included 20 consecutive HF patients receiving SGLT2i alongside optimized therapy. Transthoracic echocardiography and non-invasive bioimpedance assessments (NICaS system) were performed at baseline and after 4 weeks. Results The median patient age was 75 years [58–84], with 14 patients (70%) being overweight/obese, and only 4 patients with diabetes. The majority (65%) had HF with preserved EF (HFpEF), 25% with mildly reduced EF (HFmrEF), and 10% with reduced EF (HFrEF). At a median follow-up of 33 days [30–68], significant reductions were observed in body weight (67.65 kg [46-99.20] to 65.50 kg [46.30–97], p = 0.027) and systolic blood pressure (130 mmHg [100–150] to 116.50 mmHg [100–141], p = 0.015). Hemodynamic assessments revealed a significant decrease in total peripheral resistance index (TPRi, 3616.50 dynes·sec·cm3 [1600–5024] to 3098.50 dynes·sec·cm3 [1608–4684], p = 0.002). The left atrial volume index decreased significantly (42.84 ml/m² [27-69.40] to 41.15 ml/m² [26-62.60], p < 0.001); a significant decrease in peak tricuspid regurgitation velocity [2.52 m/Sect. (1.30–3.20]), vs. 2.21 m/Sect. (1.44–2.92), p = 0.023] and in pulmonary artery systolic pressure (PASP) [31.0 mmHg (15.0–40.0) vs. 25.50 mmHg (15.0-38.0-), p = 0.010] was observed. Patients with HFrEF or HFmrEF showed significant reduction in total body water (66.33 [51.45–74.45] vs. 58.68 [55.13–66.50]), while HFpEF patients (overweight/obese, n = 11, 79%) had a significant reduction in TPRi (3681 dynes·sec·cm3 [1600–5024] vs. 3085 dynes·sec·cm3 [1608–4684] p = 0.005). Conclusions Early hemodynamic responses to SGLT2i may differ across HF subtypes. In overweight patients with cardiometabolic HFpEF, our preliminary findings suggest an association with reduced vascular resistance, while in HFrEF/HFmrEF, the primary benefit appears to be volume unloading. However, the vascular effects of SGLT2i remain uncertain, and given the small sample size, these results should be interpreted as hypothesis-generating. Our findings also highlight the potential role of non-invasive hemodynamic monitoring in guiding therapy in HF.